The electronic and magnetic properties of wurtzite Mn:CdS, Cr:CdS Mn:Cr:CdS: first principles calculations. (July 2017) - Nabi, Azeem; Akhtar, Zarmeena; Iqbal, Tahir; Ali, Atif; Arshad Javid, Muhammad
Abstract: In this article, density functional theory (DFT) based on generalized gradient approximation (GGA) and GGA+U, U is Hubbard term, is used to study the electronic properties of CdS doped with different dopants (Cr, Mn). The calculations are carried out for Mn-doped CdS, Cr-doped CdS, and co-doping of Mn/Cr in CdS simultaneously. It is found that hopping of electrons is possible with Cr:CdS and Mn:Cr:CdS while Mn:CdS does not allow the hopping of electrons. Moreover, double exchange interactions are observed in Cr:CdS and d-d super-exchange interactions are observed in Mn:CdS. Now the problem becomes interesting when one magnetic ion (Cr) supporting double exchange interactions and another ion (Mn) supporting d-d super-exchange interactions are doped simultaneously in the same system (CdS). The co-doped CdS is more stable even at high Curie temperature due to p-d double exchange interactions and d-d super exchange interactions. Furthermore, the Cr-3d and Mn-3d states present in-between the band gap are responsible for inner shell transitions and hence for optical properties. Therefore, the co-doped system is taken into account to enhance its applications in the field of spintronic and magneto-optical devices.